2007
DOI: 10.1111/j.1398-9995.2006.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma control or severity: that is the question

Abstract: In the first National Heart Lung and Blood Institute and Global Initiative for Asthma (GINA) guidelines, the level of symptoms and airflow limitation and its variability allowed asthma to be subdivided by severity into four subcategories (intermittent, mild persistent, moderate persistent, and severe persistent). It is important to recognize, however, that asthma severity involves both the severity of the underlying disease and its responsiveness to treatment. Thus, the first update of the GINA guidelines defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 81 publications
3
48
0
10
Order By: Relevance
“…In asthma, the control level is also independent of asthma medications (128)(129)(130)(131)(132). Although such an independent relationship was suspected in a study on allergic rhinitis (67), this very important finding was confirmed in a recent study in which it was found that the severity of rhinitis is independent of its treatment (119).…”
Section: Aria Classification Of Allergic Rhinitissupporting
confidence: 55%
“…In asthma, the control level is also independent of asthma medications (128)(129)(130)(131)(132). Although such an independent relationship was suspected in a study on allergic rhinitis (67), this very important finding was confirmed in a recent study in which it was found that the severity of rhinitis is independent of its treatment (119).…”
Section: Aria Classification Of Allergic Rhinitissupporting
confidence: 55%
“…In some studies, it has been found that NAR is also associated with asthma (7,14,48). However, the importance of the association between the two sites of the airways needs to be better assessed comparing allergic and nonallergic patients, particularly in patients with uncontrolled asthma (49,50).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Asthma is of variable severity and is increasingly recognized as a condition presenting as various phenotypes [1,2]. Asthma control is the main goal of therapy and is achieved when the disease results in minimal or no symptoms, normal sleep and activities, and optimal pulmonary function [3,4]. Such control can be obtained with patient education, avoidance of environmental triggers, individualized pharmacotherapy and regular follow-up.…”
Section: Reviewmentioning
confidence: 99%